MORTGAGE AS A MEANS OF GUARANTEE - Tsintsadze, Ketevan (European Scientific Journal, ESJ, 2015)
Among all real rights granted by way of security, mortgage, as the â€œKing of Guaranteeâ€ has the special advantage. At the time with prosperous market economy, to maintain the speed and the safety of transactions is the essential task of civil and commercial law. The responsibility of maintaining the safety of transactions and decreasing the risks of transactions falls in the guarantee system (Guohua She, 2010). A mortgage is a security interest in real property held by a lender as a security for a debt, usually a loan of money. It is a transfer of an interest in land (or the equivalent) from the owner to the mortgage lender, on the condition that this interest will be returned to the owner when the terms of the mortgage have been satisfied or performed. In other words, the mortgage is a security for the loan that the lender makes to the borrower. In most jurisdictions mortgages are strongly associated with loans secured on real estate rather than on other property (such as ships) and in some jurisdictions only land may be mortgaged. A mortgage is the standard method by which individuals and businesses can purchase real estate without the need to pay the full value immediately from their own resources. The object and purpose of this article is to analyze and review development of Institute of Mortgage (Hypothec) - from the ancient Greek period till the present time, especially in those conditions, when Mortgage is real â€œKing of Guaranteeâ€ in Georgia.